2022
DOI: 10.1186/s12864-022-08848-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of the expression profiles of the lncRNA-miRNA-mRNA ceRNA network in granulosa and cumulus cells from yak ovaries

Abstract: Background Growing oocytes acquire the ability to mature through two-way communication between gametes and surrounding somatic cumulus cells (CCs). Granulosa cells (GCs) support oocyte growth, regulate meiosis progression, and modulate global oocyte transcription activity. However, the proliferation and differentiation of the yak ovary in GCs and CCs remain unclear. To characterize the important roles of long non-coding RNA, (lncRNA), microRNA (miRNA), and messenger RNA (mRNA), whole-transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The potential molecular gene network in oogenesis was conserved among different species with internal fertilization. Previous studies in Atlantic cod [ 27 ], yak [ 28 ], chickens [ 29 ], and insects [ 30 ] also reported similar pathways involved in oogenesis. In addition, in Drosophila [ 31 ], mating-induced oocyte maturation with calcium binding and transport proteins increased, as well as calcium signaling pathways that were also significantly enriched in the present study.…”
Section: Discussionmentioning
confidence: 63%
“…The potential molecular gene network in oogenesis was conserved among different species with internal fertilization. Previous studies in Atlantic cod [ 27 ], yak [ 28 ], chickens [ 29 ], and insects [ 30 ] also reported similar pathways involved in oogenesis. In addition, in Drosophila [ 31 ], mating-induced oocyte maturation with calcium binding and transport proteins increased, as well as calcium signaling pathways that were also significantly enriched in the present study.…”
Section: Discussionmentioning
confidence: 63%
“…The reaction conditions were as follows: 95°C for 5 min, followed by 40 cycles of 95°C for 30 s, 61°C for 30 s, and 72°C for 10 s, and then, by 72°C for 2 min. For each gene, four replicates were analyzed ( 13 ). The relative expression of DEGs was analyzed using the 2 −ΔΔCT method, and the data were analyzed using analysis of variance (ANOVA) on SPSS (version 24.0).…”
Section: Methodsmentioning
confidence: 99%
“…After they were blocked with skimmed milk at room temperature for 4 h, the membranes were individually incubated with primary antibodies against FOXI1, SLC12A2, and KCNMA1 (each diluted at 1:800) at 4°C overnight. Next, the membranes were washed 10 times with PBST for 5 min, followed by incubation with secondary antibodies (goat antirabbit IgG, diluted at 1:3,000) on a shaker at room temperature for 1.5 h. After another round of 10 washings with PBST for 5 min, the membranes were treated with enhanced chemiluminescence reagent for visualization; next, the images were scanned using a chemiluminescence imager ( 13 ). Band intensity analysis was performed using ImageJ, and the target bands’ grayscale values were compared with those of β-actin bands.…”
Section: Methodsmentioning
confidence: 99%
“…The target and reference primer sequences were designed using Primer Premier 6.0 ( Table 1 ). The relative expression of the target gene transcripts was calculated using the 2 −ΔΔCT method and subjected to statistical analysis using SPSS 22.0 software [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, equal amounts of protein were separated on 10% or 15% SDS-polyacrylamide gel electrophoresis and transferred to polyvinylidene difluoride (PVDF) membranes. The membranes were blocked with 5% skim milk in Tris-buffered saline containing 0.1% Tween-20 for 3 h at room temperature, incubated overnight at 4 °C with primary antibody, and on the next day, they were incubated for 45 min at room temperature with a secondary antibody (Goat Anti-Rabbit IgG-HRP) [ 23 ]. Bands were visualized using an ECL kit (AB65623, Abcam, Cambridge, UK) and detected using the Amersham Imager 600 system (GE Healthcare Life Sciences, Marlborough, MA, USA).…”
Section: Methodsmentioning
confidence: 99%